Becoming Welcoming: Organizational Collaboration and Immigrant Integration in Dayton, Ohio. (3rd April 2017) - Majka, Theo; Longazel, Jamie
Abstract : Coinciding with a national trend toward the localization of immigration law and policy, the city of Dayton, Ohio, passed the "Welcome Dayton—Immigrant Friendly City" resolution in2011 . This article focuses on the central role played by a coalition of local organizations, staffed by or advocating on behalf of immigrants and refugees, that led up to the initiative's passage and during its implementation. Characterized by collaboration, such efforts laid the groundwork for a policy that is attentive to the needs of immigrants and refugees. When they subsequently worked alongside city officials, local organizations also managed to affect meaningful local-level institutional changes. Dayton, as a result, became a leader in regional and national efforts to create more welcoming cities. Drawing mostly on several years of participant observation, the article adds to the literature on immigrant integration a rich description of the role local organizations play in the process of becoming welcoming. It also shows how an approach rooted in the humanitarian concerns of immigrants/refugees and their allies can pose a meaningful challenge to the exclusionary rhetoric and inaction that currently plague immigration law and policy.